Finansial Performance Analysis Of Fund Allocation Management Villages Based On Degree Of Decentralization Ratio, Independence Ratio, Effectiveness Ratio And Ratio Growth In Adang Buom Village Alor Regency, East Nusa Tenggara Province - Lily Andari Mukhtar; Chairil Akhyar; Muttaqien; Nurlela (PT. Radja Intercontinental Publishing, 2024)
This research aims to analyze the financial performance of village fund allocation management in terms of the degree of decentralization ratio, independence ratio, effectiveness ratio and growth ratio in Adang Buom Village, Alor Regency, East Nusa Tenggara Province. This research is quantitative research with secondary data sources. The data processed is the financial report of Village Fund Allocation in the Village Revenue and Expenditure budget from 2018 to 2022. The data collection technique used is documentation technique. The data analysis technique used in this research is descriptive statistics with the formula for degree of decentralization ratio, independence ratio, effectiveness ratio and growth ratio. The results of this research show that the ratio of the degree of decentralization and the ratio of independence is not good in managing the financial performance of village fund allocation management. while the effectiveness ratio and growth ratio are very good in managing financial performance in managing village fund allocation.